If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6v + 2 = -2(v + -5) Reorder the terms: 2 + -6v = -2(v + -5) Reorder the terms: 2 + -6v = -2(-5 + v) 2 + -6v = (-5 * -2 + v * -2) 2 + -6v = (10 + -2v) Solving 2 + -6v = 10 + -2v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '2v' to each side of the equation. 2 + -6v + 2v = 10 + -2v + 2v Combine like terms: -6v + 2v = -4v 2 + -4v = 10 + -2v + 2v Combine like terms: -2v + 2v = 0 2 + -4v = 10 + 0 2 + -4v = 10 Add '-2' to each side of the equation. 2 + -2 + -4v = 10 + -2 Combine like terms: 2 + -2 = 0 0 + -4v = 10 + -2 -4v = 10 + -2 Combine like terms: 10 + -2 = 8 -4v = 8 Divide each side by '-4'. v = -2 Simplifying v = -2
| 7h-6h=15 | | 6(w-7)-8w=-36 | | 10h-7h=18 | | 13h+7h=20 | | s-7500=18000 | | 7x+25+3x=16-2x-3 | | 8m+2=9m+4 | | 4v+3-3(-5v-1)=5(v-2) | | 2t-t=7 | | -2(-2)-7y=-2 | | 18d-15d=9 | | 4v+3-3(-5v-1)=5(v+2) | | x^3+8x^2+14x+4=0 | | 2(5x+3)=-36-4x | | 9.12*9.12= | | 10y=2y+72 | | 9.11*9.11= | | 9.15*9.15= | | -31+3a=4(a-7) | | x+3(2x+5)=6 | | -8(1+3x)-6x=172 | | n-8=19-11 | | 9.21*9.21= | | n^2-12n+13=-7 | | 3(r-5)+2(r-4)=-2(r-1)+8(r+2) | | 8(7r+5)=320 | | 6x-5=109 | | 8(7r+5)=330 | | e^4x=e^2x+6 | | 2/3=2-2 | | 2a+14-13=-7 | | a^2+8a+6=-9 |